In situ study of self-ion irradiation damage in W and W-5Re at 500 degrees C - Yi, X; Jenkins, M; Briceno, M; Roberts, S; Zhou, Z; Kirk, M (2013)
In situ self-ion irradiations (150 keV W+) have been carried out on W and W-5Re at 500°C, with doses ranging from 1016 to 10 18 W+m-2 (~1.0 dpa). Early damage formation (1016W+m-2) was observed in both materials. Black-white contrast experiments and image simulations using the TEMACI software suggested that vacancy loops were formed within individual cascades, and thus, the loop nucleation mechanism is likely to be cascade collapse. Dynamic observations showed the nucleation and growth of interstitial loops at higher doses, and that elastic loop interactions may involve changes in loop Burgers vector. Elastic interactions may also promote loop reactions such as absorption or coalescence or loop string formation. Loops in both W and W-5Re remained stable after annealing at 500°C. One-dimensional hopping of loops (b = 1/2 <111>) was only seen in W. At the final dose (1018W +m-2), a slightly denser damage microstructure was seen in W-5Re. Both materials had about 3-4 × 1015 loops m -2. Detailed post-irradiation analyses were carried out for loops of size ≥ 4 nm. Both b = 1/2 <111> (~75%) and b = <100> (~25%) loops were present. Inside-outside contrast experiments were performed under safe orientations to determine the nature of loops. The interstitial-to-vacancy loop ratio turned out close to unity for 1/2 <111> loops in W, and for both 1/2 <111> and <100> loops in W-5Re. However, interstitial loops were dominant for <100> loops in W. Re seemed to restrict loop mobility, leading to a smaller average loop size and a higher number density in the W-Re alloy. © 2013 Copyright Taylor and Francis Group, LLC.